Comparative study of lung cancer care and survival outcomes across the Nordic countries - Ghida Khalife; Juho Waris; Uffe Bødtger; Johan Isaksson; Kirill Neumann; Hrönn Harðardóttir; Heidi Andersén; Antti Jekunen; Maria Lovén; Tuula Vasankari; Susanna Nurmi-Rantala; Paulus Torkki (Acta Oncologica)
Background: Lung cancer (LC) is the leading cause of cancer-related deaths worldwide. Despite societal, economic and genetic similarities, 5-year age-standardized relative survival rate is lower in Finland compared to the other Nordic countries. Previous studies have identified discrepancies in LC guidelines, but research on actual care practices remains limited. We aim to address this knowledge gap by conducting a comprehensive examination of the current care practices for LC patients in the Nordic countries.